2007
DOI: 10.1038/sj.npp.1301403
|View full text |Cite
|
Sign up to set email alerts
|

Are GABAA Receptors Containing α5 Subunits Contributing to the Sedative Properties of Benzodiazepine Site Agonists?

Abstract: Classical benzodiazepines (BZs) exert anxiolytic, sedative, hypnotic, muscle relaxant, anticonvulsive, and amnesic effects through potentiation of neurotransmission at GABA A receptors containing a 1 , a 2 , a 3 or a 5 subunits. Genetic studies suggest that modulation at the a 1 subunit contributes to much of the adverse effects of BZs, most notably sedation, ataxia, and amnesia. Hence, BZ site ligands functionally inactive at GABA A receptors containing the a 1 subunit are considered to be promising leads for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
78
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 36 publications
4
78
1
Order By: Relevance
“…PWZ-029 exerted negligible activity in 42 other receptor and enzyme assays (B. Roth et al, NIMH Psychoactive Drug Screening Program, UNC, unpublished results, available at https://kidbdev.med.unc.edu/pdsp). The in vitro concentration-effects curves for SH-053-R-CH3-2'F, the ligand used for interaction study in the locomotor activity test, showed it is a high-efficacy agonist at the α5-containing GABA A receptors, with very low efficacies at α1, α2 and α3-containing subtypes (Rowlett, Furtmüller, Cook, unpublished data); the profile was comparable with that published for its close congener SH-053-R-CH3 (Savić et al, 2008), except for greater potencies and α5-efficacy of SH-053-R-CH3-2'F.…”
Section: Electrophysiological Experimentssupporting
confidence: 59%
See 1 more Smart Citation
“…PWZ-029 exerted negligible activity in 42 other receptor and enzyme assays (B. Roth et al, NIMH Psychoactive Drug Screening Program, UNC, unpublished results, available at https://kidbdev.med.unc.edu/pdsp). The in vitro concentration-effects curves for SH-053-R-CH3-2'F, the ligand used for interaction study in the locomotor activity test, showed it is a high-efficacy agonist at the α5-containing GABA A receptors, with very low efficacies at α1, α2 and α3-containing subtypes (Rowlett, Furtmüller, Cook, unpublished data); the profile was comparable with that published for its close congener SH-053-R-CH3 (Savić et al, 2008), except for greater potencies and α5-efficacy of SH-053-R-CH3-2'F.…”
Section: Electrophysiological Experimentssupporting
confidence: 59%
“…Based on the results with three novel BZ site agonists functionally silent at the α1 subunit, we recently set out the hypothesis that positive modulation at the GABA A receptors containing α5 subunits may contribute to sedative properties of BZ site agonists (Savić et al, 2008). The finding that SH-053-R-CH3-2'F at the lower (10 mg/kg), but not higher dose (20 mg/kg), antagonized the hypolocomotor effect of PWZ-029 adds to the notion that there may exist certain discontinuous 'effective windows' of the modulation of locomotion exerted by neurons expressing the α5-subunit containing GABA A receptors.…”
Section: Discussionmentioning
confidence: 99%
“…GABA A receptor ligands active in the central nervous system (CNS) can have many effects including anxiolytic, sedative, hypnotic, amnesic, anticonvulsant, and muscle relaxant effects. This motivated a search for benzodiazepine (BDZ) ligands that discriminate among the ␣-subunits of GABA A receptors (41,42).A novel approach to achieve this goal was developed by Cook and coworkers in the 1980s (1, 25) that employed a pharmacophore/receptor model based on the binding affinity of rigid ligands to BDZ/GABA A receptor sites (8). From this series of receptor models for ␣ 1-6 ␤3␥2 subtypes a robust pharmacophore for ␣5-subtype selective ligands emerged resulting in the synthesis of a novel ␣5␤3␥2 partial agonist modulator:…”
mentioning
confidence: 99%
“…Conversely, alpha5-GABA A receptors were insensitive and developed tolerance to the sedative actions of benzodiazepines. [21][22][23] Verkuyl et al 24) reported that expression of alpha5, not alpha1-GABA A receptors was increased in patients with hyperfunctional HPA axes. Therefore the absence of a flunitrazepam-induced hypnotic effect may be the result of tolerance developed by upregulation of alpha5-GABA A receptors in ACTH-treated rats.…”
Section: Discussionmentioning
confidence: 99%